Challenging the Evidence for Prehistoric Wetland Maize Agriculture at Fort Center, Florida. Issue 1 (20th January 2013) - Thompson, Victor D.; Gremillion, Kristen J.; Pluckhahn, Thomas J.
Abstract: The early evidence (2400 ± 105 B.P.) for wetland maize agriculture at the archaeological site of Fort Center, a large earth-work site in South Florida, USA, is frequently cited in discussions of the emergence of agriculture in the Eastern Woodlands of North America. The evidence for maize, however, rests on controversial pollen data; some researchers accept it, others remain skeptical of its identification or chronological placement. We present microbotanical data (pollen and phytoliths), macrobotanical data, and radiocarbon dates from recent excavations from this site. We argue that maize agriculture did not occur until the historic period at this site and that the identification of maize in earlier deposits is likely a result of contamination.